Role of polymers in encapsulation and shape-stabilization of phase change materials (PCMs) for thermal energy storage applications: an overview - Surya Tanwar; Raminder Kaur (Academia Materials Science)
Phase change materials (PCMs) are suitable for thermal energy storage (TES) owing to their increased heat storage ability, narrow temperature difference between storage and retrieval of latent heat energy, and readiness in a variety of phase change transition temperatures. Numerous research attempts have been made to develop a broad array of PCMs based on inorganic, organic, and polymeric compounds for a diverse area of applications. To improve the performance efficiency and proper handling of PCMs, they are often encapsulated or confined within a shape-stabilized supporting material of an inorganic or organic origin. This review emphasizes the current research status of the polymer-based PCMs developed using the various PCMs–polymer combinations available, material characteristics, encapsulation, and shape-stabilization methods and provides detailed information on the contribution of polymers toward the enhancement of PCM end-product properties, in an avant-garde technology related to TES.